Strength Improvement of Cemented Carbides by Hot Isostatic Pressing (HIP) - Engel, Ulf; Hübner, H. (Journal of Materials Science, 1978)
HIP treatment after sintering increases the strength of the investigated cemented carbide alloy by a factor of two whereas hardness, fracture toughness, and work of fracture remain unchanged. HIP does not affect the microstructural parameters of the carbide skeleton and the binder phase, but the residual pores are eliminated entirely. Failure of both the as-sintered and post-densified material occurs by a pure Griffith mechanism. The strength-flaw size relationship is established experimentally and is shown to obey exactly Griffith's basic strength equation. The strength is controlled by the largest microstructural defects, i.e. pores in the as-sintered material, and coarse WC grains and inclusions in the HIP-treated specimens. © 1978 Chapman and Hall Ltd.
LFT Import::2019-07-16 (1793)